In Vitro and In Silico Study of Analogs of Plant Product Plastoquinone to Be Effective in Colorectal Cancer Treatment - Halilibrahim Ciftci; Belgin Sever; Firdevs Ocak; Nilüfer Bayrak; Mahmut Yıldız; Hatice Yıldırım; Hasan DeMirci; Hiroshi Tateishi; Masami Otsuka; Mikako Fujita; Amaç Fatih TuYuN (Molecules, 2022)
Plants have paved the way for the attainment of molecules with a wide-range of biological activities. However, plant products occasionally show low biological activities and/or poor pharmacokinetic properties. In that case, development of their derivatives as drugs from the plant world has been actively performed. As plant products, plastoquinones (PQs) have been of high importance in anticancer drug design and discovery; we have previously evaluated and reported the potential cytotoxic effects of a series of PQ analogs. Among these analogs, PQ2, PQ3 and PQ10 were selected for National Cancer Institute (NCI) for in vitro screening of anticancer activity against a wide range of cancer cell lines. The apparent superior anticancer potency of PQ2 on the HCT-116 colorectal cancer cell line than that of PQ3 and PQ10 compared to other tested cell lines has encouraged us to perform further mechanistic studies to enlighten the mode of anti-colorectal cancer action of PQ2. For this purpose, its apoptotic effects on the HCT-116 cell line, DNA binding capacity and several crucial pharmacokinetic properties were investigated. Initially, MTT assay was conducted for PQ2 at different concentrations against HCT-116 cells. Results indicated that PQ2 exhibited significant cytotoxicity in HCT-116 cells with an IC50 value of 4.97 ± 1.93 μM compared to cisplatin (IC50 = 26.65 ± 7.85 μM). Moreover, apoptotic effects of PQ2 on HCT-116 cells were investigated by the annexin V/ethidium homodimer III staining method and PQ2 significantly induced apoptosis in HCT-116 cells compared to cisplatin. Based on the potent DNA cleavage capacity of PQ2, molecular docking studies were conducted in the minor groove of the double helix of DNA and PQ2 presented a key hydrogen bonding through its methoxy moiety. Overall, both in vitro and in silico studies indicated that effective, orally bioavailable drug-like PQ2 attracted attention for colorectal cancer treatment. The most important point to emerge from this study is that appropriate derivatization of a plant product leads to unique biologically active compounds.